(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2026)
Primary biliary cholangitis (PBC) is a chronic autoimmune cholestatic liver disease characterized by progressive destruction of small intrahepatic bile ducts. It predominantly affects middle-aged women, and occurrence in males is uncommon. We report a case of a 53-year-old male presenting with long-standing pruritus, recent onset jaundice, and pedal edema. Laboratory evaluation revealed markedly elevated alkaline phosphatase, positive antinuclear antibody (ANA), and antimitochondrial antibody (AMA) with negative viral markers and no evidence of biliary obstruction on imaging. Fibroscan suggested advanced fibrosis, and endoscopy revealed esophageal varices. A diagnosis of PBC with cirrhotic changes was made. The patient was treated with ursodeoxycholic acid along with supportive therapy. This case highlights the importance of considering PBC in male patients with cholestatic liver disease for early diagnosis and management. J Bangladesh Coll Phys Surg 2026; 44: 138-139